Students’ Perception in Listening Skill Learning by Watching English Vtubers on Youtube at SMAN 3 Mataram - Adiyatma, Dodit; I Made Sujana; Junaidi, Ahmad (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aims to perceive the benefits and the challenges of watching English VTubers on YouTube to one’s listening skills through the perception of the 12th grade students of SMAN 3 Mataram as it is the largest youngest audience of English VTubers. The subjects of the study were the 12th grade students of SMAN 3 Mataram which consists of 6 students in total who had been observed to have ample knowledge about English VTuber to gain the most accurate and reliable data. The data of the participants were collected through the use of questionnaires as the first data, interviews as the second data, and observation as the supporting data to add more credibility for the previous 2 techniques before being processed through the use of several data analysis techniques starting from trimming, coding, tabulation, and cross-case analysis. The cross-case analysis, being the final data analysis technique to be done, is the most important technique as the data from both the questionnaires and interviews will be compared to each other to gain the final results and conclusions of the study. Through the analysis, it was confirmed that according to the perception of the participants, there exist several benefits of watching English VTubers on YouTube to one’s listening skills as well as several challenges that exist to hinder the process.